KAHA Ligation at Serine. Issue 1 (24th November 2015) - Li, Yi‐Ming; Huang, Yi‐Chao; Liu, Lei
Abstract : Oxazetidine assisted KAHA ligation was developed by the Bode group as an efficient peptide segment ligation strategy at native serine residues. This milestone achievement should enable the chemical synthesis of difficult‐to‐prepare proteins for biological studies.